Aplikasi Perancangan Sistem Penilaian (Ujian) Berbasis Web Di SMP Negeri 4 Kota Solok - Rozi Meri; Silvi Lestari; Aidil Putra (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2022)
Learning is a very important element in education in Indonesia. In learning there are various kinds of strategies and methods that can be used in accordance with existing conditions. Implementation of learning strategies which include teaching, discussion, reading, assignments, presentations and evaluations. This includes online assessments with the Learning Management System (LMS). With the assessment process it is easier and more efficient. With this online/digital system (LMS), the assessment process can be carried out quickly and accurately. After students carry out the assessment, grades can immediately appear in the system. This final project aims to assist teachers and students in administering exams, especially at SMPN 4 Kota Solok. In the implementation of the exam still uses conventional methods that require quite a lot of time and effort. The role of information and communication technology that is growing rapidly, one of which is through the internet network, can be used to overcome this problem. The study conducted in this research created a website for online exam implementation. This can make it easier for teachers to upload questions that have been made for online exam implementation. The advantage of the system contained in this web is that students can immediately find out the results of the exam after ending it.